2022
DOI: 10.1177/17562848221140662
|View full text |Cite
|
Sign up to set email alerts
|

First-line treatments for advanced hepatocellular carcinoma: a network meta-analysis and cost-effectiveness analysis in China and the United States

Abstract: Background: Various therapeutic strategies are available for the first-line treatment of patients with advanced hepatocellular carcinoma (aHCC). But which approach is the most cost-effective remains uncertain. Objectives: This study aims to evaluate the cost-effectiveness of first-line strategies in aHCC patients from the perspective of Chinese and US payers. Design: A network meta-analysis (NMA) and cost-effectiveness study. Data sources and methods: A NMA was conducted to collect all first-line strategies wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…Similarly, Sun et al . 27 conducted a network meta-analysis and cost-effectiveness study of several treatment options, including lenvatinib, which was favored as the first-line treatment choice for advanced HCC from the perspectives of Chinese and US payers. Notably, the Phase III REFLECT trial that confirmed the noninferiority of lenvatinib to sorafenib excluded HCC patients with high-risk of Vp-4 portal vein tumor thrombus 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sun et al . 27 conducted a network meta-analysis and cost-effectiveness study of several treatment options, including lenvatinib, which was favored as the first-line treatment choice for advanced HCC from the perspectives of Chinese and US payers. Notably, the Phase III REFLECT trial that confirmed the noninferiority of lenvatinib to sorafenib excluded HCC patients with high-risk of Vp-4 portal vein tumor thrombus 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Sun et al . conducted a network meta-analysis with a cost-effective analysis of the first-line treatments for aHCC in China and the United States [ 27 ]. Compared to donafenib, ATE/BEV and LEN added 0.46 and 0.77 quality-adjusted life-years.…”
Section: Discussionmentioning
confidence: 99%
“…In a cost-effectiveness analysis of five systemic treatments for unresectable HCC in China, donafenib was found to be the most economical option, followed by sorafenib > LEN > sintilimab plus bevacizumab > ATE/BEV [26]. Subsequently, Sun et al conducted a network meta-analysis with a cost-effective analy-sis of the first-line treatments for aHCC in China and the United States [27]. Compared to donafenib, ATE/ BEV and LEN added 0.46 and 0.77 quality-adjusted life-years.…”
Section: Discussionmentioning
confidence: 99%
“…Sorafenib, a multitarget tyrosine kinase inhibitor (TKI) and the first approved drug for HCC patients, is most frequently used as an adjuvant therapy in resected HCC patients[ 107 ] and as a frontline systemic treatment in patients with HCC recurrence after LT. However, the current data are mainly based on observational research due to the exclusion of Randomized Protocol studies and Asia-Pacific trials of sorafenib from the registered studies for HCC[ 107 , 108 ]. Sorafenib has a few drawbacks, including poor oral bioavailability and drug toxicities, and its OS is only marginally improved by 2.8 mo[ 107 , 109 ].…”
Section: Sorafenibmentioning
confidence: 99%
“…However, the current data are mainly based on observational research due to the exclusion of Randomized Protocol studies and Asia-Pacific trials of sorafenib from the registered studies for HCC[ 107 , 108 ]. Sorafenib has a few drawbacks, including poor oral bioavailability and drug toxicities, and its OS is only marginally improved by 2.8 mo[ 107 , 109 ]. The impacts of sorafenib in patients with recurrent HCC who underwent an incurable liver transplant have been estimated in several retrospective studies.…”
Section: Sorafenibmentioning
confidence: 99%